Effects of Processing Parameters on Zinc Oxide Thin Films Prepared by Single Solution Deposition. Issue 47 (11th May 2016) - Martinez, Manuel F.; Shahriar, Shaimum; Kava, Donato; Sana, Cheik; Castaneda, Vanessa; Galindo, Jose; Hodges, Deidra R.
ABSTRACT: Zinc oxide thin films were prepared via the sol-gel spin-coating method with the use of a spin processor. The film's annealing parameters were varied to study their impact on the final film morphology and electrical properties. Characterization of the structural properties of the samples was carried on a X-ray diffractometer (XRD) and scanning electron microscopy. Electrical characterization was obtained with the use of a four point probe. Optical characterization of the samples was carried on a UV-Vis-NIR Spectrophotometer. Samples annealed under a cover are observed to have a higher transmission percentage on the visible light range while having a very small grain size and small relative resistivity. Samples annealed under standard atmospheric conditions show a larger grain size and resistivity, and correlated to it, a smaller transmission percentage. Samples annealed under vacuum prove to have a much more reduced optical, electrical, and structural properties when compared to the rest of the samples.